2020
DOI: 10.1002/jaba.706
|View full text |Cite
|
Sign up to set email alerts
|

The influence of instructive feedback presentation schedule: A replication with children with autism spectrum disorder

Abstract: Alpine Learning Group Instructive feedback (IF) is a modification to discrete trial instruction that may increase instructional efficiency for individuals with autism spectrum disorder. Several variations of IF have recently been evaluated in the literature; however, few studies have assessed the effectiveness and efficiency of presenting secondary targets on continuous versus intermittent presentation schedules. The current study evaluated the effectiveness and efficiency of various presentation schedules of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This level of attending and engagement may be important for clients to learn through direct telehealth intervention and may explain the acquisition of the observational responses and those related to the instructional feedback. Nottingham et al (2020) discussed the potential role of a bidirectional naming repertoire in the acquisition of secondary target responses without direct teaching. A bidirectional naming repertoire is a higher‐order operant in which there is a two‐way relationship between speaker and listener behaviors in which teaching one of the behaviors is enough to establish both repertoires without direct training (Horne & Lowe, 1996; Miguel, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This level of attending and engagement may be important for clients to learn through direct telehealth intervention and may explain the acquisition of the observational responses and those related to the instructional feedback. Nottingham et al (2020) discussed the potential role of a bidirectional naming repertoire in the acquisition of secondary target responses without direct teaching. A bidirectional naming repertoire is a higher‐order operant in which there is a two‐way relationship between speaker and listener behaviors in which teaching one of the behaviors is enough to establish both repertoires without direct training (Horne & Lowe, 1996; Miguel, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Discrete trial teaching (DTT) is a commonly implemented ABA procedure used to teach a variety of skills to individuals with ASD (Eikeseth et al, 2014;Leaf et al, 2016). Additionally, an increasing number of studies (e.g., Leaf et al, 2017;Nottingham et al, 2020) have demonstrated the benefits of incorporating instructive feedback into DTT. Instructive feedback is the practice of including extra nontarget (or secondary targets) stimuli in the instruction or consequence component of DTT (Werts et al, 2003).…”
mentioning
confidence: 99%
“…One potential reason for slow or lack of acquisition is the use of tangible preferred items rather than tokens or edibles, which were used in most studies on IF (e.g., Frampton & Shillingsburg, 2020 ; Loughrey et al, 2014 ; Nottingham et al, 2017 ; Nottingham et al, 2020 ; Vladescu & Kodak, 2013 ). We deviated from the procedures in Frampton and Shillingsburg ( 2020 ) to provide tangible items rather than tokens because the participants did not use token economies in their programming at the time of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of secondary targets may result in more rapid learning because learners can acquire twice (or more; Nottingham et al, 2017 ) the number of targets when IF is included (Shillingsburg et al, 2018 ). Acquisition of secondary targets with IF has been demonstrated in 1:1 and small-group instruction for several populations, including individuals of typical development and individuals with disabilities like intellectual disability, ASD, speech and language impairments, learning disabilities, developmental delays, and Down syndrome (e.g., Carroll & Kodak, 2015 ; Leaf et al, 2017 ; Nottingham et al, 2017 ; Nottingham et al, 2020 ; Tekin-Iftar, 2003 ; Tullis et al, 2022 ; Werts et al, 1995 ). Secondary target acquisition with IF has also been demonstrated with several procedural variations such as the number, location, and presentation schedule (Carroll & Kodak, 2015 ; Nottingham et al, 2017 ; Nottingham et al, 2020 ; Vladescu & Kodak, 2013 ).…”
mentioning
confidence: 99%
“…Tact emergence following stimulus pairing has also been documented in older children of typical development (e.g., Pérez-González et al, 2014;Rosales, Rehfeldt, & Huffman, 2012) and in children with language delays due to neurodevelopmental disorders (e.g., Byrne, Rehfeldt, & Aguirre, 2014;Solares & Fryling, 2018). In addition, tact emergence following stimulus pairing is a common finding in studies on the use of instructive feedback procedures, in which some acquisition targets are presented via modeling alone and often include novel tacts (see, e.g., Haq, Zemantic, Kodak, LeBlanc, & Ruppert, 2017;Nottingham, Vladescu, DeBar, Deshais, & DeQuinzio, 2020;Reichow & Wolery, 2011;Vladescu & Kodak, 2013).…”
mentioning
confidence: 97%